Influence of scion size on graft success in custard apple cv. Balanagar (Indian Journal of Arid Horticulture, 2025)
Custard apple (Annona squamosa L.) belongs to family Annonaceae and now gaining popularity on waste and dry lands. Custard apple is mainly propagated through seed and therefore, there exists a great variation in respect of growth, yield and fruit quality amongst the trees grown in the orchard. However, it is a common experience to come across individual free plant exhibiting superior fruit quality and profile yield. If such promising trees are further perpetuated vegetatively the desirable types can be multiplied and orchards with uniform fruit quality can be established. Kudmulwar et al (2008) reported that softwood grafting was effective in terms of percentage success, percent of survival, shoot length and the number of functional leaves. However the studies in respect of standardization of scion size viz., length and diameter for achieving maximum graft success through softwood grafting have yet not been carried out. Keeping the point under consideration the present study was therefore, undertaken to find out the most suitable size of scion shoot for obtaining maximum success for softwood grafting in custard apple cv. Balanagar.
Keywords: plant exhibiting; diameter; orchards; variation